2019
DOI: 10.1016/j.ebiom.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells potently purge latent HIV-1 beyond TCR-stimulation, activating the PI3K-Akt-mTOR pathway

Abstract: Background The latent HIV-1 reservoir in treated patients primarily consists of resting memory CD4 + T cells. Stimulating the T-cell receptor (TCR), which facilitates transition of resting into effector T cells, is the most effective strategy to purge these latently infected cells. Here we supply evidence that TCR-stimulated effector T cells still frequently harbor latent HIV-1. Methods Primary HIV-1 infected cells were used in a latency assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Identifying novel pathways or effector molecules involved in latency maintenance and reversal is appealing ( Figure 1 ). New findings regarding pathways related to cell longevity and immune-cell differentiation or regulatory kinase pathways and their control over transcription factors and cytokine expression during HIV latency are crucial [ 78 , 79 , 112 ]. Therefore, the involvement of pro- and anti-apoptotic proteins and their interactions with viral proteins in immune cells during latent HIV infection warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identifying novel pathways or effector molecules involved in latency maintenance and reversal is appealing ( Figure 1 ). New findings regarding pathways related to cell longevity and immune-cell differentiation or regulatory kinase pathways and their control over transcription factors and cytokine expression during HIV latency are crucial [ 78 , 79 , 112 ]. Therefore, the involvement of pro- and anti-apoptotic proteins and their interactions with viral proteins in immune cells during latent HIV infection warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR) protein is a serine/threonine protein kinase that belongs to the PI3K-related kinase family and is associated with a wide range of cellular processes such as cell proliferation, motility, growth, and survival, as well as protein synthesis and gene transcription. The interactions between dendritic cells and T cells through cell surface receptors/ligands, which activate PI3K-Akt-mTOR signaling by triggering dephosphorylation of proteins downstream of the Akt signaling pathway [ 112 ], play an important role in HIV latency reversal. However, such activation does not increase the expression/activity of nuclear transcription factors, such as NF-κB.…”
Section: Hiv Latency and Potential Agents For Reversalmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to optimize the "shock and kill" approach, recent findings revealed that interaction of infected CD4+ T cells with DC could activate latent HIV-1 [99]. The contact with dendritic cells also activates the PI3K-Akt-mTOR pathway in CD4+ T cells and contributes to HIV-1 purge.…”
Section: Mtorc1 In Hiv-1 Latencymentioning
confidence: 99%
“…Although the incorporation of antigen in DC-mediated LR has been underexplored, Marini et al successfully utilized iDCs loaded with SEB superantigen for reactivation of HIV-1 in in vitro-infected CD4 + T cell lines [221]. Furthermore, van Montfort and colleagues determined that iDCs in combination with TCR stimulation more efficiently reversed latency in primary HIV-infected cells from aviremic individuals than TCR activation alone, a phenomenon that was dependent on PI3K-Akt-mTOR pathway activation [228]. Finally, a study investigating the latency activation potential of various DC subsets demonstrated that tissue-resident and blood-derived myeloid DCs reactivated virus in vitro from latently infected effector T cells with different efficiencies [229].…”
Section: Lra Potential Of Dcsmentioning
confidence: 99%